Penentu penerimaan petani dalam inovasi penanaman padi melalui kaedah projek estet padi dan sistem intensifikasi padi - Nur Badriyah, Kamarul Zaman (2018)
Rice is an important commodity in Malaysia as it is the most prominent staple food for the population. Therefore, the target of increasing the rice production of farmers has always been the main policy of the Malaysian government, in line with the year to year increase of the Malaysian population. One of the efforts to increase rice production is by applying innovation in rice cultivation management either through innovation in production or innovation in the production process. One of the management innovations in the country's rice granary area is the implementation of the Paddy Estate Project (PEP). The objective of the programme is to increase rice production with a lower operation cost. Meanwhile, the management innovation that is practised outside the rice granary area that does not have a complete irrigation system is the System of Rice Intensification (SRI) technique. It is generally known that a programme will not succeed if the target group does not receive the necessary support and assistance. Hence, this study aims to identify the determinants of the acceptance of PEP management innovation and SRI techniques among farmers. The logit regression method was used to identify the key factors determining the farmers‟ acceptance of the PEP. Meanwhile, face to face interviews were conducted to identify the farmers‟ acceptance of the SRI technique. The research findings indicate that the key factors determining the farmers‟ acceptance of the PEP are age, secondary jobs, effective communication with the extension agency, increased rice yield, lower operation cost, lower working time in the fields, and support services such as assistance and incentive facilities from the government. Meanwhile, the key factors determining the farmers‟ acceptance of the SRI technique is increased in rice yield, lower operation cost, reduced water usage, encouragement by government agencies and health awareness.